An analysis of Islamic banking performance using Maqasid shariah index: Evidence from Malaysia and Indonesia / Fahmi Ali Hudaefi - Fahmi Ali , Hudaefi (2018)
The purpose of this research was to analyse the performance of Islamic banking in actualising Maqāṣid al-Sharī‘ah in the banking industry. In doing so, this research employed a mixed method research approach. This research firstly employed the study of Maqāṣid al-Sharī‘ah index pioneered by Mohammed, Razak, & Taib (2008) to compute samples’ performance ratios, followed with simple additive weighting approach. Further quantitative approach was conducted using the approach of law of sines on Maqāṣid al-Sharī‘ah based performance initiated by Bedoui (2012), to illustrate samples’ overall orientation on Maqāṣid al-Sharī‘ah performance into a triangle figure. Following this, the qualitative approach was conducted to study relevant information communicated within samples reports which indicates their achievement in the quantitative analysis. The findings from the quantitative analysis were varied in terms of the highest and the lowest performing samples. Meanwhile, the findings from the qualitative analysis further supported the evidences of the samples’ achievement in the quantitative analysis. This research presented three contributions to the research of Islamic banking performance analysis. One, this research offered an appropriate interpretation towards Islamic banking performance analysed using Maqāṣid al-Sharī‘ah index. Two, this research provided significant information describes Islamic banks achievement in the present Maqāṣid al-Sharī‘ah index analysis. Three, the findings of this research offered a fresh insight into the achievement of Islamic banks in actualising Maqāṣid al-Sharī‘ah in the banking industry of Malaysia and Indonesia. With this, the findings of this research is hoped to assist the stakeholders of Islamic banking to appropriately understand the performance of Islamic banks under the framework of Maqāṣid al-Sharī‘ah index.